2015
DOI: 10.1002/14651858.cd010206.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Palliative pharmacological sedation for terminally ill adults

Abstract: BackgroundTerminally ill people experience a variety of symptoms in the last hours and days of life, including delirium, agitation, anxiety, terminal restlessness, dyspnoea, pain, vomiting, and psychological and physical distress. In the terminal phase of life, these symptoms may become refractory, and unable to be controlled by supportive and palliative therapies specifically targeted to these symptoms. Palliative sedation therapy is one potential solution to providing relief from these refractory symptoms. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
124
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(140 citation statements)
references
References 37 publications
8
124
0
8
Order By: Relevance
“…While euthanasia shortens life, palliative sedation does not shorten life 41. Maltoni et al argued that palliative sedation, when appropriately indicated and correctly used to relieve unbearable suffering, does not have any detrimental effect on survival of patients with terminal cancer 42 43.…”
Section: Introductionmentioning
confidence: 99%
“…While euthanasia shortens life, palliative sedation does not shorten life 41. Maltoni et al argued that palliative sedation, when appropriately indicated and correctly used to relieve unbearable suffering, does not have any detrimental effect on survival of patients with terminal cancer 42 43.…”
Section: Introductionmentioning
confidence: 99%
“…However, palliative sedation is a potential solution in the control of end-of-life refractory symptoms. 25 However, even though the increase in opioid and benzodiazepine doses during and after extubation does not reduce the time until death, this method should be used with caution. The fact that, when symptoms are well controlled, there is a lesser need to indicate palliative sedation.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the study reports discussed the "settling" of symptoms in an anecdotal way; however, there were no quantitative reports' [34] (p. 15). 'Terminally ill people experience a variety of symptoms in the last hours and days of life, including delirium, agitation, anxiety, terminal restlessness, dyspnoea, pain, vomiting, and psychological and physical distress.…”
Section: "My Husband Was Ill and He Found It Very Difficult That We Smentioning
confidence: 99%
“…In the terminal phase of life, these symptoms may become refractory, and unable to be controlled by supportive and palliative therapies specifically targeted to these symptoms. Palliative sedation therapy is one potential solution to providing relief from these refractory symptoms' [34] In a recent study from France, health care providers found that in many cases midazolam failed to provide relief from some refractory symptoms. Also deep sedation broke down the patient/carer relationship [35].…”
Section: "My Husband Was Ill and He Found It Very Difficult That We Smentioning
confidence: 99%